Hollow microspherical MXene / Sn-S / PANI composite material and preparation method and application thereof
Patent Information
- Application Number
- CN202410067002.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-01-17
AI Technical Summary
[0009]针对现有技术中采用的模板SiO2微球,从而导致需要氢氟酸去除的问题,以及PS纳米球存在带负电荷,与MXene相互排斥的问题,本发明采用PMMA微球作为模板,由于PMMA微球具有表面带正电荷、粒径较大、分散均匀、容易完全去除的特点,可以使2D MXene形成均匀分散的MXene微球,从而解决2D MXene易堆叠问题,即同时克服现有文献3和现有文献4存在的问题,最终实现提升气敏性能的效果
[0047]1、本发明采用PMMA微球作为模板,由于具有表面带正电荷、粒径较大、分散均匀、容易完全去除的特点,避免了其他模板需要在氢氟酸环境去除及与MXene排斥,可以使2DMXene形成均匀分散的MXene微球,显著解决2D MXene易堆叠问题,能够提供更多的活性位点,利于提升材料的气敏性能;
Smart Images

Figure CN117890438B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sensor technology, specifically to a hollow microsphere MXene / Sn-S / PANI composite material, its preparation method, and its application. Background Technology
[0002] Ammonia, as a common toxic and harmful gas, not only pollutes the environment but also endangers human health. Therefore, it is necessary to design a gas sensor capable of detecting ammonia at room temperature.
[0003] MXenes, as a novel 2D material, possess unique electronic structures, abundant exposed functional groups, and specific nanosheet structures, making them suitable as gas sensing materials operating at room temperature. Due to the formation of acidic functional groups on the surface of MXenes after strong acid etching, they exhibit unique selectivity for alkaline gases such as NH3. For example, existing literature 1 (Meng W, Meng H, Qianku H, et al. Tisub3 / subCsub2 / sub MXene-Based Sensors with High Selectivity for NHsub3 / sub Detection at Room Temperature.[J].ACS Sensors,2019,4(10):2763-2770.) developed an MXene-based sensor. Although this sensor can distinguish NH3 from other gases at room temperature, its selectivity is poor.
[0004] Therefore, to improve the selectivity of the sensor, it can be enhanced by loading other compounds. For example, existing literature 2 (Tai, H., Duan, Z., He, Z., Li, X., Xu, J., Liu, B., & Jiang, Y. (2019). Enhance dammonia response of Ti3C2T nanosheets supported by TiO2 nanoparticles at room temperature. Sensors and Actuators B: Chemical, 126874.) designed an MXene composite membrane-based gas sensor with added TiO2 to enhance the gas sensitivity of traditional MXene to NH3. Although this technical solution achieved a 3% response rate to 10ppm NH3 under low LOD conditions, the sensitivity still cannot meet the application requirements. The reason is that the strong van der Waals pressure on the surface of traditional 2D MXene sheets often leads to self-stacking.
[0005] To address the issue of 2D MXene stacking, its morphology can be improved by using a template method. Existing literature 3 (Mu G, Mu D, Wu B, et al. Microsphere-like SiO2 / MXene hybrid material enabling high performance anode for lithium ion batteries[J]. Small, 2020, 16(3): 1905-430.) uses spray drying to physically combine SiO2 microspheres and MXene to form MXene microspheres. This technique successfully modulates the microstructure of MXene from 2D sheets to microspheres. However, using SiO2 as a template introduces a new technical problem—SiO2 microspheres, when used as a template, require a hydrofluoric acid environment for removal. Inhalation of hydrofluoric acid vapor or skin contact can cause irreversible damage to the human body.
[0006] For example, existing literature 4 (Wei X, Song G, Li M, et al. Enhanced thermal conductivity of epoxy composites using hollow spheres MXene frameworks[J]. Composites Communications, 2023, 43: 101729.) prepared MXene hollow sphere / epoxy resin composite FMX / EX frameworks using electrostatic self-assembly and a sacrificial polystyrene PS template method. This technical solution successfully adjusted the microstructure of some MXenes from two-dimensional sheets to nanospheres. However, using polystyrene PS as a template led to a new technical problem—PS nanospheres have small particle size and negative charge, which repel MXenes, resulting in most MXenes remaining in sheet form.
[0007] Furthermore, since most detection environments, such as breath gas detection, contain a large amount of water vapor, NH3 gas sensors require stable moisture resistance. For example, existing literature 5 (CN116380988A, An MXene / MoS2 / polypyrrole composite material and its preparation method and application) uses PPy in-situ polymerization to coat the MXene / MoS2 composite material. This technical solution successfully improved the response rate of the MXene / MoS2 composite material to NH3 through PPy coating. However, using PPy as the coating layer also leads to the aforementioned technical problem—PPy's rapid protonation process results in poor moisture resistance, causing the composite material to have a low response rate in high humidity environments. Summary of the Invention
[0008] The purpose of this invention is to provide a hollow microsphere MXene / Sn-S / PANI composite material, its preparation method, and its application.
[0009] To address the issues of existing technologies using SiO2 microspheres as templates, which necessitates hydrofluoric acid removal, and the negative charge of PS nanospheres causing repulsion with MXene, this invention employs PMMA microspheres as templates. PMMA microspheres, with their positively charged surface, large particle size, uniform dispersion, and ease of complete removal, can form uniformly dispersed MXene microspheres, thus solving the problem of 2D MXene stacking. This simultaneously overcomes the problems present in existing literature 3 and 4, ultimately improving gas-sensing performance.
[0010] The specific function of each component is as follows:
[0011] 1. Using MXene spheres as a substrate not only solves the problem of easy stacking of traditional 2D MXene, but also utilizes its large number of oxygen-containing functional groups to achieve the function of room temperature ammonia gas sensing.
[0012] 2. Using Sn-S nanosheets as a loading material provides sulfur-containing acidic functional groups, which improves the material's selectivity to ammonia. On the other hand, the loading of nanosheets plays a supporting role, increasing the specific surface area of the material and thus increasing the number of active sites, thereby improving the response to ammonia.
[0013] 3. Using PANI as a coating layer has two advantages: firstly, the conductive polymer itself undergoes a protonation / deprotonation process when it comes into contact with ammonia, which significantly improves the response; secondly, PANI as a coating layer can effectively prevent the internal material from oxidizing.
[0014] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:
[0015] A hollow microsphere MXene / Sn-S / PANI composite material is obtained by combining MXene spheres, Sn-S and PANI. MXene is transformed from two-dimensional sheet to microsphere, MXene / Sn-S is microsphere, and Sn-S nanosheets of uniform size are loaded on the surface. PANI is then coated on the outside of MXene / Sn-S to obtain the hollow microsphere MXene / Sn-S / PANI composite material with a particle size of 1.5-2μm.
[0016] A method for preparing hollow microsphere MXene / Sn-S / PANI composite material includes the following steps:
[0017] Step 1, Preparation of MXene microspheres: First, titanium aluminum carbide is mixed with 30% hydrofluoric acid and etched in a water bath under certain conditions. After water bath etching, MXene is obtained by filtration, washing and drying. Then, MXene is placed in deionized water to form an MXene dispersion. Finally, using polymethyl methacrylate (PMMA) as a template, and with MXene and PMMA meeting a certain mass ratio, PMMA is placed in the MXene dispersion and mixed and stirred under certain conditions to form MXene microspheres.
[0018] In step 1, the conditions for water bath etching are: water bath temperature of 30-50℃ and water bath time of 12-36h.
[0019] In step 1, the mass ratio of MXene to PMMA is 1:10;
[0020] In step 1, the mixing conditions are: a mixing speed of 1000 r / min and a mixing time of 30 min.
[0021] Step 2, Sn-S loading: First, the MXene microspheres obtained in Step 1 are placed in a mixed solution of ethanol and ethylene glycol and sonicated under certain conditions to obtain a suspension. Then, MXene microspheres, thiourea, and tin tetrachloride pentahydrate are placed in the suspension in a certain molar ratio and subjected to a hydrothermal reaction under certain conditions. After the reaction is complete, the mixture is centrifuged under certain conditions, dried under certain conditions, and finally calcined under certain conditions to obtain MXene / Sn-S hollow microspheres.
[0022] In step 2, the conditions for ultrasound are: ultrasound power of 300-500W and ultrasound time of 2h.
[0023] In step 2, the molar ratio of MXene microspheres, thiourea, and tin tetrachloride pentahydrate is 1:2:2.
[0024] In step 2, the hydrothermal reaction conditions are: hydrothermal temperature of 150℃ and hydrothermal time of 10-15h.
[0025] In step 2, the centrifugation conditions are: centrifugation speed of 3500 r / min and centrifugation time of 5-10 min.
[0026] In step 2, the drying conditions are: drying temperature of 60-80℃ and drying time of 12-48h.
[0027] In step 2, the calcination conditions are as follows: under argon gas conditions, the calcination temperature is 350℃, and the calcination time is 0.5-1.5h.
[0028] Step 3, PANI coating: The MXene / Sn-S obtained in Step 2 is placed in H2SO4 and stirred for 30 minutes to obtain a mixed solution. At the same time, ammonium persulfate is pre-cooled in an ice-water mixture. Then, under stirring conditions, aniline and ammonium persulfate are added to the mixed solution in sequence to obtain a reaction solution. Finally, under stirring conditions and certain conditions, the reaction solution is subjected to a polymerization reaction to obtain hollow microsphere MXene / Sn-S / PANI composite material, abbreviated as MXene / Sn-S / PANI.
[0029] In step 3, the mass ratio of MXene / Sn-S to aniline is 114:50;
[0030] In step 3, the polymerization conditions are: polymerization temperature of 0-5℃ and polymerization time of 6h.
[0031] A method for fabricating an MXene / Sn-S / PANI sensor involves first mixing and grinding MXene / Sn-S / PANI with anhydrous ethanol to obtain a mixture; then, dropping the mixture onto the surface of a gold interdigitated electrode and spin-coating it; finally, connecting the gold interdigitated electrode to a gas chamber to obtain an MXene / Sn-S / PANI sensor, i.e., a gas-sensitive testing system.
[0032] The obtained MXene / Sn-S / PANI sensor showed a response rate of 60-120% to 100ppm NH3 under room temperature and 45% humidity conditions, with a response time of 220-230s and a recovery time of 270-280s.
[0033] Under humidity conditions of 0-90%, the response rate to 100 ppm NH3 is 10-220%.
[0034] An application of an MXene / Sn-S / PANI sensor as a sensor for unknown ammonia concentration includes the following steps:
[0035] Step a, obtaining standard concentration data, involves conducting an ammonia concentration detection experiment under known and determined temperature, humidity, and ammonia concentration conditions to obtain standard ammonia concentration data;
[0036] Step b, determination of unknown concentration: Under the given temperature and humidity conditions, the ammonia gas of unknown concentration is tested in an ammonia concentration detection experiment. The test results are compared with the standard ammonia concentration data to confirm the concentration of the ammonia gas to be tested.
[0037] The technical effects of this invention have been tested experimentally, and the specific details are as follows:
[0038] XRD tests on the MXene / Sn-S / PANI composite material showed that MXene / Sn-S / PANI contains characteristic peaks of MXene and SnS2, while the characteristic peaks of PANI could not be detected due to its amorphous state.
[0039] SEM testing of the MXene / Sn-S / PANI composite material showed that MXene / Sn-S / PANI is a hollow microsphere, with PANI coating the surface of the hollow microsphere MXene / Sn-S composite material.
[0040] EDS testing of the MXene / Sn-S / PANI composite material showed that, in addition to the C and Ti elements of MXene and the Sn and S elements of Sn-S, the hollow microspheres of MXene / Sn-S / PANI also contain N and O elements.
[0041] The optimal gas-sensing performance test of the MXene / Sn-S / PANI composite material showed that...
[0042] An experiment on ammonia concentration detection based on the MXene / Sn-S / PANI sensor was conducted under the following conditions: ammonia gas of known concentration was introduced into the gas chamber at a temperature of 25℃ and a humidity of 45%. The detection limit of the MXene / Sn-S / PANI sensor was 10 ppm. Furthermore, the following conclusions can be drawn: the resistance and responsivity of the MXene / Sn-S / PANI sensor increase with increasing ammonia concentration.
[0043] To demonstrate the response-recovery performance of the MXene / Sn-S / PANI sensor, response-recovery tests were conducted. The response time was 226.6 s, and the recovery time was 273.7 s, indicating that the MXene / Sn-S / PANI sensor exhibits relatively fast response and recovery characteristics.
[0044] To demonstrate the effect of humidity on the MXene / Sn-S / PANI-based sensor, humidity effect tests were conducted. Under humidity conditions ranging from 0% to 90%, the MXene / Sn-S / PANI-based NH3 gas sensor exhibited a response rate that increased with increasing humidity in the air.
[0045] To demonstrate the selectivity of the MXene / Sn-S / PANI sensor for ammonia, gas concentration detection experiments were conducted using NO2, CO2, H2, H2S, and HCHO. At room temperature, the MXene / Sn-S / PANI sensor showed the following response rates to 100 ppm of gas: NO2 25.6%; CO2 7.5%; H2 1.2%; H2S 18.2%; and HCHO 11.3%. These test results demonstrate the selectivity of the MXene / Sn-S / PANI sensor for ammonia.
[0046] Based on the above test results, the present invention has the following advantages over the prior art:
[0047] 1. This invention uses PMMA microspheres as templates. Due to their positive surface charge, large particle size, uniform dispersion, and easy complete removal, they avoid the need for other templates to be removed in a hydrofluoric acid environment and their repulsion with MXene. This allows 2D MXene to form uniformly dispersed MXene microspheres, significantly solving the problem of easy stacking of 2D MXene, providing more active sites, and improving the gas-sensing performance of the material.
[0048] 2. This invention can control the microstructure of composite materials by adjusting the synthesis ratio. The hollow microsphere composite material obtained has Sn-S sheets on the surface of the microspheres, which can provide more active sites and improve the gas-sensing performance of the material.
[0049] 3. In the hollow microsphere MXene / Sn-S / PANI composite material of this invention, the protonation process of PANI is relatively slow, which greatly improves the moisture resistance of the material and changes the response rate from decreasing with increasing humidity to increasing with increasing humidity.
[0050] 4. The hollow microsphere MXene / Sn-S / PANI-based NH3 gas sensor of this invention can quantitatively test the concentration of ammonia. Attached image description:
[0051] Figure 1 Here is the SEM image of MXene in Example 1;
[0052] Figure 2 The image shows the SEM image of MXene / Sn-S in Example 1.
[0053] Figure 3 The image shows a SEM image of the MXene / Sn-S hollow microspheres in Example 1.
[0054] Figure 4 The XRD pattern of MXene / Sn-S / PANI in Example 1;
[0055] Figure 5 The image shows the SEM image of MXene / Sn-S / PANI in Example 1.
[0056] Figure 6 The image shows a SEM image of the hollow microspheres MXene / Sn-S / PANI in Example 1.
[0057] Figure 7 The EDS spectrum of MXene / Sn-S / PANI in Example 1;
[0058] Figure 8 The resistivity curve of MXene / Sn-S / PANI to ammonia concentration in Example 1;
[0059] Figure 9 The curve showing the response rate of MXene / Sn-S / PANI to ammonia concentration in Example 1;
[0060] Figure 10 The curve of the response recovery time of MXene / Sn-S / PANI to ammonia in Example 1;
[0061] Figure 11 The effect of humidity on ammonia response rate in MXene / Sn-S / PANI in Example 1;
[0062] Figure 12 This is a selectivity diagram of MXene / Sn-S / PANI for ammonia and other gases in Example 1;
[0063] Figure 13 This is a comparison chart of the response rates of Example 1, Comparative Example 1, and Comparative Example 2 to different concentrations of ammonia. Detailed Implementation
[0064] The present invention will be further described in detail through embodiments and with reference to the accompanying drawings, but this is not intended to limit the scope of the invention.
[0065] Example 1
[0066] A method for preparing hollow microsphere MXene / Sn-S / PANI composite material includes the following steps:
[0067] Step 1, Preparation of MXene microspheres: First, titanium aluminum carbide is mixed with 30% hydrofluoric acid and etched in a water bath at 40°C for 24 hours. After etching, MXene is obtained by filtration, washing and drying. Then, 0.5g of MXene is placed in deionized water to form an MXene dispersion. Finally, using polymethyl methacrylate (PMMA) as a template, with a mass ratio of MXene to PMMA of 1:10, 5g of PMMA is placed in the MXene dispersion and mixed at a stirring rate of 1000r / min for 30 minutes to form MXene microspheres.
[0068] To demonstrate the microstructure of MXene microspheres, i.e., the successful preparation of MXene microspheres, SEM testing was performed. The test results are as follows: Figure 1 As shown, MXene is in the form of microspheres. Test results show that the template method in step 1 can transform MXene from a two-dimensional sheet into a microsphere.
[0069] Step 2, Sn-S loading: First, the MXene microspheres obtained in Step 1 were placed in a mixed solution of ethanol and ethylene glycol and sonicated at an ultrasonic power of 500W for 2 hours to obtain a suspension. Then, thiourea and tin tetrachloride pentahydrate were placed in the suspension at a molar ratio of 1:2:2 and subjected to a hydrothermal reaction at a hydrothermal temperature of 150℃ for 12 hours. After the reaction was completed, the mixture was centrifuged at a centrifugation speed of 3500 r / min for 5 minutes and then dried at a drying temperature of 60℃ for 24 hours. Finally, the mixture was calcined under argon gas conditions at a calcination temperature of 350℃ for 1 hour to obtain MXene / Sn-S hollow microspheres.
[0070] To verify the microstructure of the MXene / Sn-S hollow microspheres, SEM testing was performed. The test results are as follows: Figure 2 As shown, MXene / Sn-S is a microsphere with uniformly sized nanosheets on its surface. Combining SEM and EDS results confirms that the nanosheet structure is Sn-S, i.e., Sn-S nanosheets.
[0071] To further demonstrate the microstructure of the MXene / Sn-S hollow microspheres, i.e., their hollow structure, the MXene / Sn-S hollow microspheres obtained in step 2 were cut and subjected to SEM testing. The test results are as follows: Figure 3 As shown, MXene / Sn-S has a hollow structure, that is, MXene / Sn-S hollow microspheres.
[0072] Step 3, PANI coating: 100 mg of MXene / Sn-S obtained in Step 2 was placed in 30 mL of 0.5 M H2SO4 and stirred for 30 min to obtain a mixed solution. At the same time, ammonium persulfate was pre-cooled in an ice-water mixture. Then, under stirring conditions, 220 μL of aniline and 285 mg of ammonium persulfate were added to the mixed solution in sequence to obtain a reaction solution. Finally, under stirring conditions, the reaction solution was subjected to a polymerization reaction at a polymerization temperature of 3 °C and a polymerization time of 6 h to obtain hollow microsphere MXene / Sn-S / PANI composite material, abbreviated as MXene / Sn-S / PANI.
[0073] To confirm the composition of MXene / Sn-S / PANI, XRD tests were performed. The test results are as follows: Figure 4 As shown, MXene / Sn-S / PANI contains characteristic peaks of MXene and SnS2, while the characteristic peaks of PANI cannot be detected because it is amorphous.
[0074] Therefore, to further confirm the composition of the MXene / Sn-S / PANI hollow microspheres, i.e., the successful encapsulation of PANI, EDS testing was performed. The test results are as follows: Figure 7 As shown, the MXene / Sn-S / PANI hollow microspheres contain not only C and Ti elements of MXene and Sn and S elements of Sn-S, but also N and O elements. Test results indicate that step 3 successfully coated the surface of the MXene / Sn-S hollow microspheres with PANI.
[0075] The successful preparation of MXene / Sn-S / PANI can be confirmed by XRD and EDS tests.
[0076] To demonstrate the microstructure of MXene / Sn-S / PANI, specifically the effect of PANI coating on the microstructure, SEM testing was performed. The test results are as follows: Figure 5 As shown, PANI is coated on the surface of hollow microsphere MXene / Sn-S composite material.
[0077] To further demonstrate the microstructure of the MXene / Sn-S / PANI hollow microspheres, i.e., their hollow structure, the MXene / Sn-S / PANI hollow microspheres obtained in step 3 were cut and subjected to SEM testing. The test results are as follows: Figure 6 As shown, MXene / Sn-S / PANI has a hollow structure, namely, MXene / Sn-S / PANI hollow microspheres.
[0078] To demonstrate that MXene / Sn-S / PANI has the ability to detect ammonia, i.e., it can be used as an ammonia sensor, a sensor based on MXene / Sn-S / PANI was prepared, and gas concentration detection experiments were conducted.
[0079] A method for preparing an MXene / Sn-S / PANI sensor involves first mixing and grinding 6 mg of MXene / Sn-S / PANI with 1 mL of anhydrous ethanol to obtain a mixture; then, adding 20 μL of the mixture to the surface of a gold interdigitated electrode and spin-coating it; finally, connecting the gold interdigitated electrode to a gas chamber to obtain an MXene / Sn-S / PANI sensor, i.e., a gas-sensitive testing system.
[0080] A performance testing method based on the MXeneSn-S / PANI sensor, referred to as the gas concentration detection experiment, is an application of the MXene / Sn-S / PANI sensor as an ammonia sensor. The specific method involves introducing a certain concentration of gas into a gas chamber under certain temperature and humidity conditions, measuring the resistance of the MXene / Sn-S / PANI sensor, and calculating the response rate.
[0081] An experiment on ammonia concentration detection based on an MXene / Sn-S / PANI sensor was conducted. The specific test conditions were: a temperature of 25℃ and a humidity of 45%. Ammonia of known concentrations was introduced into the gas chamber for ammonia concentration detection. The test results are shown in Table 1. Figure 8 and Figure 9 As shown, the detection limit based on the MXene / Sn-S / PANI sensor is 10 ppm; and the following conclusions can be drawn: the resistance and responsivity based on the MXene / Sn-S / PANI sensor increase with increasing ammonia concentration.
[0082] Table 1. Changes in resistance and response rate of the MXene / Sn-S / PANI sensor to different concentrations of ammonia at room temperature.
[0083] 0 0 0 5 442 16.65 10 1196 45.07 20 1304 49.11 30 1584 59.68 40 1850 69.68 50 2101 79.15 100 3179 119.76
[0084] To demonstrate the response-recovery performance of the MXene / Sn-S / PANI sensor, response-recovery tests were conducted. The test results are as follows: Figure 10 As shown, the response time is 226.6s and the recovery time is 273.7s, which means that the MXene / Sn-S / PANI sensor has the characteristics of fast response and recovery.
[0085] To demonstrate the impact of humidity on the MXene / Sn-S / PANI-based sensor, humidity effect tests were conducted. Test results for humidity levels ranging from 0% to 90% are shown below. Figure 11As shown in Table 2, there is a pattern that the response rate increases with increasing humidity in the air.
[0086] Table 2. Effect of humidity on the response rate of MXene / Sn-S / PANI sensor
[0087] 100 0 10.9 100 30 48.76 100 60 183.82 100 90 215.18
[0088] To demonstrate the selectivity of the MXene / Sn-S / PANI sensor for ammonia, gas concentration detection experiments were conducted using NO2, CO2, H2, H2S, and HCHO, respectively. At room temperature, the MXene / Sn-S / PANI sensor exhibited a response rate of [missing value] to 100 ppm of gas. Figure 12 As shown in Table 3, the response rate for NO2 was 25.6%; for CO2, 7.5%; for H2, 1.2%; for H2S, 18.2%; and for HCHO, 11.3%. These test results demonstrate that the MXene / Sn-S / PANI sensor exhibits selectivity for ammonia.
[0089] Table 3 Selectivity Test Table for MXene / Sn-S / PANI Sensors
[0090] <![CDATA[NH3]]> 100 119.76 <![CDATA[H2]]> 100 1.2 <![CDATA[NO2]]> 100 25.6 <![CDATA[CO2]]> 100 7.5 <![CDATA[H2S]]> 100 18.2 HCHO 100 11.3
[0091] An application of an MXene / Sn-S / PANI sensor as a sensor for unknown ammonia concentration includes the following steps:
[0092] Step a, obtaining standard concentration data, involves conducting an ammonia concentration detection experiment under known and determined temperature, humidity, and ammonia concentration conditions to obtain standard ammonia concentration data;
[0093] Step b, determination of unknown concentration: Under the given temperature and humidity conditions, the ammonia gas of unknown concentration is tested in an ammonia concentration detection experiment. The test results are compared with the standard ammonia concentration data to confirm the concentration of the ammonia gas to be tested.
[0094] To demonstrate the effect of the aniline addition ratio on performance, Comparative Example 1 and Comparative Example 2 are provided, with aniline addition ratios of 57:50 and 171:50 mass ratios of aniline to MXene / Sn-S, respectively.
[0095] Comparative Example 1
[0096] A composite material of MXene / Sn-S / PANI with a mass ratio of aniline to MXene / Sn-S of 57:50 is provided. The steps are the same as those in Example 1 unless otherwise specified, except that the amount of aniline added in step 3 is 1.25 mmol. The resulting material is named MXene / Sn-S / PANI-1.25.
[0097] The ammonia concentration detection results of MXene / Sn-S / PANI-1.25 are as follows: Figure 13 As shown in Table 4, the response rate of MXene / Sn-S / PANI-1.25 to 100 ppm ammonia at room temperature is 79.5%, which is lower than the response rate of MXene / Sn-S / PANI-2.5 to ammonia under the same conditions. This is because the amount of PANI added is relatively small, failing to completely encapsulate the MS, causing the MS to play a major role in the gas-sensing performance, resulting in a lower response rate to ammonia.
[0098] Comparative Example 2
[0099] A composite material of MXene / Sn-S / PANI with an aniline and MXene / Sn-S mass ratio of 171:50 is provided. The steps are the same as those in Example 1 unless otherwise specified, except that the amount of aniline added in step 3 is 3.75 mmol, and the resulting material is named MXene / Sn-S / PANI-3.75.
[0100] The ammonia concentration detection results of MXene / Sn-S / PANI-3.75 are as follows: Figure 13 As shown in Table 4, the response rate of MXene / Sn-S / PANI-3.75 to 100 ppm ammonia at room temperature was 63.38%, which is much lower than the response rate of MXene / Sn-S / PANI-2.5 to ammonia under the same conditions. This is because excessive PANI addition resulted in excessive coating of MS, leading to a reduction in the number of exposed active sites and thus a lower response rate to ammonia.
[0101] Table 4 Comparison of Response Rates between Example 1 and Comparative Example
[0102] 0 0 0 0 10 45.46 28.61 26.15 20 49.47 32.1 26.81 30 59.68 37.97 31.18 40 69.68 43.94 36.51 50 79.06 51.7 41.52 100 119.76 79.5 63.38
[0103] By comparing Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that the addition ratio of aniline has a significant impact on the gas-sensing properties of the MXene / Sn-S / PANI composite material.
Claims
1. A method for preparing hollow microsphere MXene / Sn-S / PANI composite material, characterized in that... Includes the following steps: Step 1, Preparation of MXene microspheres: First, titanium aluminum carbide is mixed with 30% hydrofluoric acid and etched in a water bath under certain conditions. After water bath etching, MXene is obtained by filtration, washing and drying. Then, MXene is placed in deionized water to form an MXene dispersion. Finally, using polymethyl methacrylate (PMMA) as a template, and with MXene and PMMA meeting a certain mass ratio, PMMA is placed in the MXene dispersion and mixed and stirred under certain conditions to form MXene microspheres. In step 1, the mass ratio of MXene to PMMA is 1:10; Step 2, Sn-S loading: First, the MXene microspheres obtained in Step 1 are placed in a mixed solution of ethanol and ethylene glycol and sonicated under certain conditions to obtain a suspension. Then, MXene microspheres, thiourea, and tin tetrachloride pentahydrate are placed in the suspension in a certain molar ratio and subjected to a hydrothermal reaction under certain conditions. After the reaction is complete, the mixture is centrifuged under certain conditions, dried under certain conditions, and finally calcined under certain conditions to obtain MXene / Sn-S hollow microspheres. In step 2, the molar ratio of MXene microspheres, thiourea, and tin tetrachloride pentahydrate is 1:2:
2. Step 3, PANI coating: The MXene / Sn-S obtained in Step 2 is placed in H2SO4 and stirred for 30 min to obtain a mixed solution. At the same time, ammonium persulfate is pre-cooled in an ice-water mixture. Then, under stirring conditions, aniline and ammonium persulfate are added to the mixed solution in sequence to obtain a reaction solution. Finally, under stirring conditions and certain conditions, the reaction solution is subjected to a polymerization reaction to obtain hollow microsphere MXene / Sn-S / PANI composite material, abbreviated as MXene / Sn-S / PANI. In step 3, the mass ratio of MXene / Sn-S to aniline is 114:50; The resulting hollow microsphere MXene / Sn-S / PANI composite material is obtained by combining MXene spheres, Sn-S and PANI. MXene is transformed from two-dimensional sheet to microsphere, MXene / Sn-S is microsphere, and Sn-S nanosheets of uniform size are loaded on the surface. PANI is then coated on the outside of MXene / Sn-S to obtain the hollow microsphere MXene / Sn-S / PANI composite material with a particle size of 1.5-2μm.
2. The preparation method according to claim 1, characterized in that: In step 1, the conditions for water bath etching are: water bath temperature of 30-50℃ and water bath time of 12-36 h. In step 1, the mixing conditions are: a mixing rate of 1000 r / min and a mixing time of 30 min.
3. The preparation method according to claim 1, characterized in that: In step 2, the conditions for ultrasound are: ultrasound power of 300-500W and ultrasound time of 2 hours. In step 2, the hydrothermal reaction conditions are: hydrothermal temperature of 150℃ and hydrothermal time of 10-15h. In step 2, the centrifugation conditions are: centrifugation speed of 3500 r / min and centrifugation time of 5-10 min. In step 2, the drying conditions are: drying temperature of 60-80℃ and drying time of 12-48h. In step 2, the calcination conditions are as follows: under argon gas conditions, the calcination temperature is 350℃, and the calcination time is 0.5-1.5h.
4. The preparation method according to claim 1, characterized in that: In step 3, the polymerization conditions are: polymerization temperature of 0-5℃ and polymerization time of 6 h.
5. The method for fabricating a sensor using the MXene / Sn-S / PANI obtained according to claim 1, characterized in that: First, MXene / Sn-S / PANI and anhydrous ethanol are mixed and ground to obtain a mixture. Then, the mixture is dropped onto the surface of the gold interdigitated electrode and spin-coated. Finally, the gold interdigitated electrode is connected to the gas chamber to obtain a gas-sensitive testing system based on the MXene / Sn-S / PANI sensor.
6. The MXene / Sn-S / PANI-based sensor obtained by the method for preparing the sensor according to claim 5, characterized in that: Under room temperature and 45% humidity conditions, the response rate to 100ppm NH3 is 60-120%, the response time is 220-230s, and the recovery time is 270-280s. Under humidity conditions of 0-90%, the response rate to 100ppm NH3 is 10-220%.
7. The application of the MXene / Sn-S / PANI sensor as an unknown ammonia concentration sensor according to claim 6, characterized in that... Includes the following steps: Step a, obtaining standard concentration data, involves conducting an ammonia concentration detection experiment under known and determined temperature, humidity, and ammonia concentration conditions to obtain standard ammonia concentration data; Step b, determination of unknown concentration: Under the given temperature and humidity conditions, the ammonia gas of unknown concentration is tested in an ammonia concentration detection experiment. The test results are compared with the standard ammonia concentration data to confirm the concentration of the ammonia gas to be tested.
Citation Information
Patent Citations
MXene / MoS2 / polypyrrole composite material as well as preparation method and application thereof
CN116380988A
Preparation method of tin disulfide / graphene / tin dioxide ternary composite gas sensing material for nitrogen dioxide gas-sensitive sensor
CN108181355A
Wearable conductive film sensor and preparation method and application thereof
CN113720884A
MXene / Bi2O3 heterojunction microsphere, membrane material containing MXene / Bi2O3 heterojunction microsphere and application of membrane material in oily wastewater
CN116966846A